Wire-guided exchange of an inside stent for complex biliary stricture after living donor liver transplantation - Tsuyoshi Hamada; Takeshi Tsujino; Hiroyuki Isayama; Yukiko Ito; Ryo Nakata; Satoshi Ogata; Masatoshi Makuuchi; Kazuhiko Koike (Turkish Journal of Gastroenterology, 2019)
-